Comparison of safer and metric-based actual evapotranspiration models in a subtropical area of Brazil - SILVA, César de Oliveira Ferreira [UNESP]; Manzione, Rodrigo Lilla [UNESP]; Filho, José Luiz Albuquerque (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2019)
Remote sensing algorithms are well known to estimate surface energy fluxes in regional to global scales with low cost. The remote sensing approach has an advantage of estimating evapotranspiration (ET) on larger spatiotemporal scales when compared with traditional methods. This study compared the result of ET estimates from the “Simple Algorithm for Evapotranspiration Retrieving” (SAFER) and “Mapping Evapotranspiration at high Resolution with Internal Calibration” (METRIC) models on varied land uses of a subtropical area located in Southeast Brazil by using a image from the sensor OLI of LANDSAT-8. The results showed similarity of ET estimate from both models, although slight deviation especially at high ET values. It happened due differences as the need of anchor pixel in METRIC, which requires two points with extrem thermohydrological conditions in the same area. Minimum ground data requirement is the major advantage of the METRIC over the SAFER model. The maximum value, the sum and ET range by METRIC was higher than SAFER. This study has considered both models feasible for estimation of ET from satellite data in the study area.
Comparação de modelos de evapotranspiração real safer e metric em uma área subtropical do Brasil
Keywords: Agriwater; Landsat-8; Modelling; Remote sensing; Superficial temperature